Análise da influência do zinco nas propriedades mecânicas do ferro fundido cinzento G2500. - Chimendes, Nilis Cunha (2019)
Gray cast iron is widely used in the automotive industry, which has a high requirement for mechanical and metallurgical properties, precisely because they are part of the construction of components with a high level of criticality. The smelters use scrap as one of the components for the preparation of metal loads and, because of the high availability of galvanized scrap on the market, the zinc steels are present in this preparation. However, the effects of zinc on the mechanical properties of gray cast iron are not yet fully understood. Aiming to evaluate these effects, four specimens were leaked by varying the chemical composition of the zinc and keeping the other process parameters constant. It was carried out a mass balance by adding zinc in the molds in the form of metallic zinc powder, being carried out later tests of traction, hardness and metallography, seeking to identify changes in the mechanical properties, matrix and morphology of the graphite. For the methodology and composition range studied, it was not possible to observe variations in the mechanical and metallurgical properties of G2500 gray cast iron.